The effect of the menstrual cycle on exercise metabolism: Implications for exercise performance in eumenorrhoeic women - Oosthuyse, T.; Bosch, A. N. (Sports Medicine, 2010)
The female hormones, oestrogen and progesterone, fluctuate predictably across the menstrual cycle in naturally cycling eumenorrhoeic women. Other than reproductive function, these hormones influence many other physiological systems, and their action during exercise may have implications for exercise performance. Although a number of studies have found exercise performance - and in particular, endurance performance - to vary between menstrual phases, there is an equal number of such studies reporting no differences. However, a comparison of the increase in the oestrogen concentration (E) relative to progesterone concentration (P) as the E/P ratio (pmol/nmol) in the luteal phase in these studies reveals that endurance performance may only be improved in the mid-luteal phase compared with the early follicular phase when the E/P ratio is high in the mid-luteal phase. Furthermore, the late follicular phase, characterized by the pre-ovulatory surge in oestrogen and suppressed progesterone concentrations, tends to promote improved performance in a cycling time trial and future studies should include this menstrual phase. Menstrual phase variations in endurance performance may largely be a consequence of changes to exercise metabolism stimulated by the fluctuations in ovarian hormone concentrations. The literature suggests that oestrogen may promote endurance performance by altering carbohydrate, fat and protein metabolism, with progesterone often appearing to act antagonistically. Details of the ovarian hormone influences on the metabolism of these macronutrients are no longer only limited to evidence from animal research and indirect calorimetry but have been verified by substrate kinetics determined with stable tracer methodology in eumenorrhoeic women. This review thoroughly examines the metabolic perturbations induced by the ovarian hormones and, by detailed comparison, proposes reasons for many of the inconsistent reports in menstrual phase comparative research. Often the magnitude of increase in the ovarian hormones between menstrual phases and the E/P ratio appear to be important factors determining an effect on metabolism. However, energy demand and nutritional status may be confounding variables, particularly in carbohydrate metabolism. The review specifically considers how changes in metabolic responses due to the ovarian hormones may influence exercise performance. For example, oestrogen promotes glucose availability and uptake into type I muscle fibres providing the fuel of choice during short duration exercise; an action that can be inhibited by progesterone. A high oestrogen concentration in the luteal phase augments muscle glycogen storage capacity compared with the low oestrogen environment of the early follicular phase. However, following a carbo-loading diet will super-compensate muscle glycogen stores in the early follicular phase to values attained in the luteal phase. Oestrogen concentrations of the luteal phase reduce reliance on muscle glycogen during exercise and although not as yet supported by human tracer studies, oestrogen increases free fatty acid availability and oxidative capacity in exercise, favouring endurance performance. Evidence of oestrogen's stimulation of 5'-AMP-activated protein kinase may explain many of the metabolic actions of oestrogen. However, both oestrogen and progesterone suppress gluconeogenic output during exercise and this may compromise performance in the latter stages of ultra-long events if energy replacement supplements are inadequate. Moreover, supplementing energy intake during exercise with protein may be more relevant when progesterone concentration is elevated compared with menstrual phases favouring a higher relative oestrogen concentration, as progesterone promotes protein catabolism while oestrogen suppresses protein catabolism. Furthermore, prospective research ideas for furthering the understanding of the impact of the menstrual cycle on metabolism and exercise performance are highlighted.